Edukacja regionalna w dobie globalizacji. Problem budowania wspólnot lokalnych - wybrane aspekty = Regional education in globalization. The problem of building local communities - selected aspects - Tureczek, Marceli (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Regional education suffers from a lack of integration as well as short-term dependence on political and economic factors. In effect, we are dealing with a low, fragmented level of regional activity, instead of the coherence of economic policy and social policy it should be creating. These factors refer both to the policies of the state and to the activity and innovation of local governments.
Keywords: polityka regionalna; edukacja; globalizacja; społeczeństwo; regional policy; education; globalization; society